Penerapan Akuntabilitas Dan Maslahat Dalam Perspektif Hukum Wakaf - Muhammad Zuhirsyan (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2020)
This study aims to find out the application of accountability and benefits in waqf law and also to find out the urgency of recording waqf in the perspective of Islamic law and accountability in disclosure. The object of the research is the implementation of waqf in Medan City community. This is a descriptive qualitative research. The method of collecting the data in research uses library research and interviews with several related parties. The sampling technique uses random sampling. The type of data used in this study is secondary primary data. The data analysis used is descriptive by using literature studies in the form of muamalah fiqh books including the DSN-MUI fatwa. The results showed that Waqf is one of the legal actions that have been determined by rules, harmony and conditions, both in the perspective of classical Jurisprudence and legislation in Indonesia. The application of waqf law as a legal act in the perspective of benefit and accountability can be realized by recording waqf up to reporting the development of waqf management to the Indonesian Waqf Agency (IWA) or it can be conveyed directly to the public.Keywords: Waqf, Accountability, Benefits